How Does the COVID-19 Pandemic Affect Transport-Related Diesel Consumption in the U.S.? - Xinyi Wu; Yan Zhou; Zifeng Lu; Xin He (Findings)
Understanding how energy usage reacts to the COVID-19 pandemic is essential to making strategic policy decisions. This study aims to quantify the pandemic’s influences on diesel consumption and explore the potential causes of the differences across regions. We found various levels of reduction in diesel consumption at the state level during the pandemic in the U.S. Many factors, including COVID-19 cases and commodities being moved, are associated with these reductions. In particular, at the state level, more truck/train shipping of minerals, coal, and forest products associates with fewer truck activities and greater decreases in diesel consumption.